PENERAPAN METODE BIL QOLAM DALAM MENINGKATKAN PEMAHAMAN DAN KECEPATAN MEMBACA AL QUR’AN PADA GURU TPQ SE KECAMATAN REJOSO - Sofiyulloh (Center of Education Journal (CEJou), 2024)
The Implementation of the Bil Qolam Method in Enhancing the Quality of Quran Reading Skills among TPQ Teachers in Rejoso Sub-district is a research that has the following research focuses: 1. How is the process of implementing the Bil-Qolam method in TPQs across Rejoso Sub-district? 2. What are the supporting and inhibiting factors affecting the implementation of the Bil-Qolam method in TPQs across Rejoso Sub-district? 3. How can the quality of Quranic recitation by teachers be improved in the Bil-Qolam method at TPQs across Rejoso Sub-district? In this study, the researcher employed a descriptive qualitative method, with primary data sources based on Islamic education centers (TPQ) in the Rejoso sub-district that utilize the Bil Qolam method. The results of this research are: The method of reading the Quran Bil Qolam is introduced with various insights in different TPQs. Deep understanding of the meaning and Tajweed of the Quran is emphasized by the teachers, in line with the constructivist approach that highlights the active role of students in learning. The commitment of teachers and the earnestness of students create a conducive learning environment. Nevertheless, challenges such as lack of understanding among some teachers and the creation of a conducive learning environment are hurdles that need to be addressed. In conclusion, enhancing understanding and consistency in the implementation of the Bil Qolam method is expected to yield positive outcomes in Quranic learning at TPQs. Keywords: Implementation, Bil Qolam, Al-Qur'an. Abdul Majid Khon. Praktikum Qira‟at :Keanehan Bacaan Al-Quran Qira‟at Ashim Dari Hafash. Jakarta; Abdul Majid Khon, 2011. Ahmad Syarifuddin. Mendidik Anak Membaca, Menulis, Dan Mencintai Al-Quran. Jakarta; Gema Insani, 2004. Amin Syukur. Pengantar Studi Islam. Semarang: Pustaka Nuun, 2010. Basori Alwi Murtadho. Bil Qolam Al-Musamma Metode Praktis. Malang; Aula Pustaka, 2014. Bil Qolam Al Musamma. Malang; Aula Pustaka, 2014. Djam’an Satori dan Aan Komariah. Metodologi Penelitian Kualitatif. Bandung; Alfabeta, 2013. Miles,M.B, Huberman,A.M, dan Saldana, J. Qualitative Data Analysis. Jakarta; UI Press, 2014. Strategi Menghafal Al-Qur’an,. Yogyakarta; Idea Press, 2009. Nurul Ramadhani Makarao. Metode Mengajar Bidang Kesehatan. Alfabeta, 2009. Pesantren Ilmu Al-Qur’an. Buku Panduan Pembelajaran Metode Bil Qolam. Singosari, Malang: PIQ Koordinator Pusat, 2016. Metode Dan Tehnik Pembelajaran Partisipatif. Bandung; Falah Prodution, 2010. Metodologi Pengajaran Agama Islam. Jakarta; Kalam Mulya, 2001. Metode Penelitian Kuantitatif, Kualitatif Dan R&D. Bandung; PT Remaja Rosdakarya, 2018. Metode Jibril. Malang; Ikapiq, 2005. Tim Pusat Metode Bil-Qolam. Buku Paduan Praktis Belajar Al Quran Bil Qolam. Singosari, Malang: PIQ Singosari, 2004. Wina Sanjaya. Perencanaan Dan Desain Sistem Pembelajarn. Jakarta; Kencana Premada, 2009. Zulkifli. Metodologi Pengajaran Bahasa Arab. Pekanbaru: Zanafa Publising, 2011.